Principles of Forming A Healthy Lifestyle Among Students Through Physical Education and Sports - Yormatov G‘ulomjon Sattorovich (Zien Journals, 2022)
In this article, the structure of human organs and the irfunctional maturity. Internal organs, nerves and movement, musculoskeletal system, control of body harmony and their functional activity
Keywords: Hygiene rules; physical education; internal organs; nerves and movement